Entre caminhos estreitos e longas caminhadas: trajetória de mulheres Kaiowá na Ñade ru Morangatu - CAMILA ASSAD CATELAN (2022)
The current research objective comprehend the Kaiowá’s spatial mobility through the perspective of the women leadership of the community Ñande Ru Marangatu, located in the county of Antônio João. The theme articulates a spatial mobility through the gender category. The Guarani’s groups have a practice called oguatá, that means walking, and indicates the mobility that occurs among members of the same ethnic group about a wide spatiality that includes their territories. The motivation for that mobility are various, traditionally occurring owing to kindred visitations and the participation in meeting or ceremonies, for example, that shows the sociability between various communities. Through the literature review articulated with the data constructed in the research field, especially about the life stories of three young womens that today have the role of political leadership in the tekoha that they live, was possible conclude that the traditional mobility present among the Kaiowá keeps happening, and is added by new motivations related to contemporaries demands that indigenous women have been taking over, like search for studies, work, and the own political mobility. The territorial perspective is also fundamental in this research, once the mobility and spatiality become themes directly related, highlighting the relational aspect that the Kaiowá’s territories presuppose, once they are drawn through the own mobility of their members. Keywords: Indigenous Peoples. Kaiowá spatiality. Mobility. Genre.